Impact of Viral Marketing and Brand Knowledge on Consumer Purchase Decisions: A Quantitative Study: Dampak Pemasaran Viral dan Pengetahuan Merek terhadap Keputusan Pembelian Konsumen: Sebuah Studi Kuantitatif - Ayuni, Deva; Purwanto, Nuri (Indonesian Journal of Law and Economics Review, 2023)
This study investigates the influence of viral marketing and brand knowledge on purchasing decisions among users of skincare products. With a focus on students at an educational institution, quantitative research methods were employed, and data from 100 respondents were analyzed using SPSS. The findings reveal that viral marketing and brand knowledge each exert a positive and significant impact on purchasing decisions. Moreover, when considered together, viral marketing and brand knowledge jointly contribute significantly to shaping consumer purchasing decisions. This study underscores the relevance of these factors in the cosmetics industry, emphasizing their potential to drive consumer choices and inform marketing strategies. Highlight: Consumer Decision-Making Dynamics: This study delves into the intricate interplay between viral marketing, brand knowledge, and their combined influence on consumer purchasing decisions within the skincare product market. Academic Context as a Valid Setting: Focusing on students at an educational institution provides a unique lens to examine consumer behavior, offering valuable insights for both academia and industry practitioners. Practical Implications for Marketing Strategies: The findings underscore the pivotal role of viral marketing and brand knowledge in informing effective marketing strategies, emphasizing their potential to shape consumer preferences and drive purchasing decisions in the cosmetics industry. Keyword: Viral Marketing, Brand Knowledge, Purchasing Decisions, Skincare Products, Quantitative Research